Prevalence of syphilis and chlamydia trachomatis infection among men who have sex with men in Jiangsu province, China: A cross-sectional survey - Hu, Haiyang; Chen, Yuheng; Shi, Lingen; Liu, Xiaoxia; Xu, Zhuping; Sun, Lin; Zhao, Xiuping; Zhou, Ying; Lu, Jing; Zhang, Zhi; Liu, Xiaoyan; Fu, Gengfeng (Frontiers in Public Health, 2022)
Background Epidemics of sexually transmitted infections (STIs) among men who have sex with men (MSM) are major global public health concerns. This study aimed to examine the prevalence of syphilis and chlamydia trachomatis (CT) infection and associated factors among MSM in Jiangsu province, China, hoping to provide updated data for the formulation of relevant policies. Methods A cross-sectional survey was conducted among MSM from April to July 2021 in four cities in the province. Socio-demographic characteristics and behavioral information were collected through a face-to-face questionnaire interview. Venous blood specimens were collected for HIV, hepatitis C (HCV), and syphilis testing using serological testing methods. First-void urine specimens were collected for CT and Neisseria gonorrhoeae (NG) testing using nucleic acid amplification testing (NAAT) methods. Chi-square tests were used to compare differences in syphilis and CT infection between subgroups of variables. Multivariate logistic regression analysis was used to identify factors associated with syphilis and CT infection. Results A total of 1,087 participants were enrolled. The prevalence of HIV, HCV, syphilis, CT and NG infection were 6.6, 0.4, 6.3, 4.2, and 0.4%, respectively. MSM recruited online [adjusted odds ratio (aOR) = 2.189, P = 0.020], diagnosed with an STI in the past 12 months (aOR = 3.304, P < 0.001), and living with HIV (aOR = 4.721, P < 0.001) were more likely to have syphilis infection. MSM who were younger than 25 years (aOR = 4.286, P = 0.020), had senior high school level education (aOR = 2.521, P = 0.038), and were recruited via VCT clinics (aOR = 3.455, P = 0.001) were more likely to have CT infection. Conclusions Our study showed a high prevalence of syphilis and chlamydia among MSM in Jiangsu province, China. STI screening, diagnosis, and treatment services promotion should be a top priority on the prevention agenda.